Sistem Aguron-Guron Di Banjar Umadiwang Desa Batannyuh, Kecamatan Marga, Kabupaten Tabanan - Ida Bagus Putu Eka Suadnyana (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2022)
The purpose of Aguron-guron is gaining knowledge, teacher instructions, learn to discipline prostration. Associated with Aguron-guron system is in Banjar Umadiwang, Batannyuh Village, Marga District, Tabanan Regency in the conduct of a lesson (aguron- guron) studied Weda knowledge by learning the Nabe, there are a lot of moral education and the sacred values ​​that must be known and studied. Based on the above problems, the problems in this study can be formulated as follows: ( 1 ) How does the system or form Aguron - guron in Banjar Umadiwang , Batannyuh Village, Marga District, Tabanan Regency, (2 ) What is the process Aguron Umadiwang-guron in Banjar, village Batannyuh, Marga District, Tabanan Regency. Theory is used to solve the problem of the study was the theory of structuralism , theory of value , the theory of constructivism. To provide answers to the issues raised in this study, used qualitative research. Techniques of data collection using observation techniques, interviews, literature. For descriptive data analysis techniques used. a result of the research , as follows :(1) Aguron-guron System or form practiced in Banjar Umadiwang, which is based on kinship, in the sense of the Guru Nabe with sisya have a very close relationship, which is equally bound by the rules Pangasraman. (2) Aguron-guron process a series of such ceremonies to purify themselves before studying with nabe, followed by a ceremony performed by muspa Diksita candidate, candidate faces to the teacher Diksita nabe, nabe teacher candidates Commemoration diksita, tetebus ceremony, ceremony majaya-jaya, last sisya mapamit on foot worship teacher nabe.